The restriction impacts of the Type III restriction-modification system on the transmission dynamics of antimicrobial resistance genes in Campylobacter jejuni - Qiu, Yu; Guo, Pengbo; Tian, Hui; Zhou, Ye; Wen, Hongling; Liang, Hao (Frontiers in Microbiology, 2025)
IntroductionThe spread of antibiotic resistance genes among Campylobacter jejuni (C. jejuni) is a serious problem, and the effects of the restriction-modification (R-M) system on the transmission dynamics of these genes in C. jejuni remain poorly understood.Materials and methodsComplete genome sequences of C. jejuni strains were extracted from the BV-BRC database until March 25, 2024. The phylogenetic and the resistance analysis were used to analyze the distribution of resistance genes in C. jejuni. The impacts of the R-M systems on the AMR genes transmission between C. jejuni strains and the possible mechanisms were explored through recombination, pangenome and mobile genetic elements analysis.ResultsC. jejuni strains carrying the Type III R-M system have a significantly lower number of antimicrobial resistance (AMR) genes compared to strains without this system (p < 0.0001), with covariance value being −0.0526. The recombination analysis also shows that the median number of the number of AMR genes in the strains not possessing the Type III R-M system increases by 19.38% compared to strains carrying that system (p < 0.0001). We also find that the horizontal gene transfer frequency might have limited relationship with the Type III R-M system in C. jejuni through pangenome and mobile genetic elements analysis.ConclusionOur research indicates that the Type III R-M system might restrict the transmission of AMR genes potentially by affecting recombination in C. jejuni, which provides a theoretical basis for addressing the drug resistance problem.